2011
DOI: 10.1038/ejhg.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple independent variants in 6q21-22 associated with susceptibility to celiac disease in the Dutch, Finnish and Hungarian populations

Abstract: International audienceCeliac disease is an inflammatory enteropathy caused by intolerance to gluten. Previous linkage studies in the Dutch, Finnish and Hungarian populations have revealed a locus on chromosome 6q21-22 conferring susceptibility to celiac disease. This locus has previously been implicated in susceptibility to other autoimmune diseases such as Crohn's disease and type 1 diabetes. We performed finemapping on 446 independent individuals with celiac disease and 641 controls of Dutch origin, testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…32 Recently, the 6q21-22 region, which contains HACE1, has been confirmed as a celiac disease susceptibility locus (possibly mutated). 33 In our series, loss could not be identified by array comparative genomic hybridization, and loss frequency was observed in only 6% (1/16) of cases by FISH. Therefore, the loss of 6q is not characteristic of EATL cases in Japan and may be useful for exclusion of peripheral T-cell lymphoma, not otherwise specified and Extranodal NK/T lymphoma, nasal type.…”
Section: Discussioncontrasting
confidence: 65%
“…32 Recently, the 6q21-22 region, which contains HACE1, has been confirmed as a celiac disease susceptibility locus (possibly mutated). 33 In our series, loss could not be identified by array comparative genomic hybridization, and loss frequency was observed in only 6% (1/16) of cases by FISH. Therefore, the loss of 6q is not characteristic of EATL cases in Japan and may be useful for exclusion of peripheral T-cell lymphoma, not otherwise specified and Extranodal NK/T lymphoma, nasal type.…”
Section: Discussioncontrasting
confidence: 65%
“…The most popular genotyping chip, the Affymetrix 6.0 array, contains nearly 1 million SNPs, yet only one-third of these SNPs resides in the coding regions. Even though many GWAS-identified statistically significant SNPs lie in the intron or intergenic regions, [35] their biological function remains difficult to explain. Another limitation of genotyping arrays is that, because the SNPs are predetermined on the array, no finding of novel SNPs is possible.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that rs9391227 in the HACE1 gene was associated with celiac disease involved in the immune system and antigen presentation [51]; while another study revealed that five SNPs (rs17065302, rs11759010, rs6927608, rs4946645 and rs4245525) within HACE1 gene associated with equol-producing phenotype such as blood pressure [23] which may implicate HACE1 in immune responses. However, rs9391227 [51] was not available in both the case-control and family-based samples; while equol-producing phenotype associated five SNPs [23] were not associated with the risk or the AAO of AD in the case-control study and rs6927608 was not associated with the risk and AAO of AD in both samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, rs9391227 [51] was not available in both the case-control and family-based samples; while equol-producing phenotype associated five SNPs [23] were not associated with the risk or the AAO of AD in the case-control study and rs6927608 was not associated with the risk and AAO of AD in both samples. However, rs9391227 had strong LD with three AAO associated SNPs (rs7746856, rs6941988 and rs7770002 with r 2 =1.0, 1.0 and 0.87, respectively) in the case-control study (Figure 5); whereas rs6927608 had weak LD with other SNPs (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 99%